KAJIAN KONSENTRASI EKSTRAK TANAMAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza sativa L.) - andi fajarwanto; Siswadi Siswadi; Dewi Ratna Nurhayati (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
Research on the study of the concentration of plant extracts on the growth and yield of rice plants was carried out in April - July 2020, located in Pare Village, Mondokan District, Sragen Regency with an altitude of 150 masl with grumosol soil type. This study aims: to see the effect of plant extracts on the growth and yield of rice plants, to measure the best extracts on the growth and yield of rice plants. This study used a randomized group (RAKL) single factor plant extract with various concentrations that resulted in 10 different treatments. A0K0: without presenting plant extracts, A1: Bamboo shoot extract, A2: Banana hump extract, A3: Onion extract, K1: 20ml / l concentration, K2: 40ml / l concentration, K3: 60ml / l concentration. The treatment was repeated 3 times in order to get 30 experimental experiments. The experimental unit of a treatment consisting of 4 clumps of plants. Observations were made on the treatment plots. To see no effect of the effect of plant extracts, a test through analysis of variance was used. Meanwhile, to determine the significance of the treatment, the Duncan test was used at level of 5%. The results showed (1)Bamboo shoots, banana weevil and shallot plant extracts were able to increase the number of tillers per clump by 19% compared to the control but did not affect plant height, leaf color, panicle length, number of grains per clump, grain weight per clump and weight of 1000 grains . (2)Bamboo shoots, banana weevil and shallot plant extracts were able to increase the number of clump panicles by 23% compared to the control but did not affect plant height, leaf color, panicle length, number of grains per clump, grain weight per clump and weight of 1000 grains.